The Effectiveness of PSS (Problem Solving Strategy) in enhancing the ability of anger regulation - Ferisa Prasetyaning Utami; Permata Sari; Siti Zahra Bulantika; Ike Kurnia Ani Khusana; Citra Tectona Suryawati; Nisa Ariantini (Konselor, 2020)
The purpose of this research is to examine the effectiveness of Problem Solving Strategies (PSS) in enhancing the ability of emotion regulation for high school students. This study was carried out at Malang Smart Brawijaya High School with a sample size of 12 students equally divided into the experimental (n = 6) and control (n = 6) groups. Furthermore, the experimental group was trained on Problem Solving Strategies, contrary to the control group. Data were analyzed using Mann Whitney U Test, which is a non-parametric statistical analysis tool. The result showed that the Asymp or P-value of 0.003 <0.05, therefore, there is a significant difference between the post-test scores in the experimental and control groups. In conclusion, the Problem-Solving Strategy is an effective technique for enhancing the ability of anger regulation.  School counselors are encouraged to utilize Problem Solving Strategies as intervention techniques to enhance anger regulation. Further research needs to be carried out using behavioralistic techniques.